129 The role of cardiopulmonary exercise testing in patients undergoing heart transplantation. (4th June 2021) - Chatrath, Nikhil; Jones, Timothy; Cole, Denise; Dar, Owais
Abstract : Introduction: The role of cardiopulmonary exercise testing (CPET) in assessing patients with advanced heart failure (HF) is well established. Exercise capacity is a validated marker of quality of life in this cohort of patients. This study aimed to assess changes in CPET parameters in patients undergoing Heart Transplantation (HTx), subdividing outcomes by underlying aetiology of HF. Methods: A single-centre, retrospective analysis of CPET data including baseline haemodynamic parameters, exercise time (ET), peak oxygen consumption (VO2) and respiratory exchange ratio (RER) of all patients undergoing HTx between July 2011 and December 2018 was conducted. Pre and post-HTx CPET parameters were compared and correlation between Pre-HTx CPET parameters and 1-year mortality was analysed. Results: 199 patients underwent HTx, 138 (69.3%) male, with a median age at transplant of 46 years. Advanced dilated cardiomyopathy (DCM) 62.8% (n=125) and ischaemic cardiomyopathy (ICM) 18.6% (n=37) were the leading indications for HTx. 35 (17.6%) were bridged to transplant with Ventricular Assist Devices (VAD) .Being unable to perform CPET pre-HTx was a predictor of 1-year mortality post HTx; RR 1.65 (95%CI 1.06-2.56; p=0.024). However, when CPET was performed, a low pre-HTx VO2 (<14 ml/kg/min) was not a predictor of 1-year mortality; RR 0.93 (95% CI 0.508-1.715, p=0.824). Pre-HTx and 1 year post-transplant CPET data was available for 77 patients. HTx significantly increased the number of patients achieving greater than 50% predicted VO2; 86.1% pre-HTx vs 30.7% post-HTx (p=0.001). There was a mean increase in VO2 of 6.94 ml/kg/min per patient (95% CI 5.79-8.08; p=0.001).When subdivided by underlying HF aetiology, there was no significant difference in the degree of improvement in VO2; 58.9% post-HTx improvement in VO2 in patients with ICM vs 62.2% for patients with non-ischaemic DCM (p=0.24).For the subgroup of patients (n=42) who had serial CPETs, the improvements in VO2 were seen within the first 3 years post-HTx, before reaching a plateau after 3 years ( figure 1 ). Conclusion: Patients pre-HTx should be counselled on the objective improvement in exercise capacity seen in this study, as a marker of improved quality of life post-HTx, regardless of the underlying HF aetiology. The inability to perform CPET pre-HTx is associated with higher peri-operative mortality. This study also highlights the importance of CPET to risk-stratify patients pre-HTx Conflict of Interest: None